Environmental micropollutants - Hashmi, Muhammad Zaffar; Wang, Shuhong; Ahmed, Zulkfil (Advances in pollution research., 2022)
Environmental Micropollutants, the latest volume in the Advances in Environmental Pollution Research series, presents the latest research on various environmental micropollutants, as well as their impacts on health and the economy, also addressing the best possible solutions to address the risks presented by these pollutants. The book covers solutions for dusts, infectious particles, heavy metals, organophosphates, atmospheric toxic organic micropollutants, fungal spores, pollutants from E-waste, and antibiotics threats, providing researchers working in environmental science and management with key knowledge to address this increasingly important concern. These types of micropollutants can be present in water, air and soil and can harm health even in low quantities, hence this book covers the challenges these pollutants pose to the environment and human health, presenting practical solutions.